Safety and Efficacy of Nemolizumab for Patients with Pruritus: A Systematic Review and Meta-Regression Analysis of Randomized Controlled Trial - Liang, Junqin; Hu, Fengxia; Dan, Maoli; Sang, Yingbing; Abulikemu, Kailibinuer; Wang, Qian; Hong, Yongzhen; Kang, Xiaojing (Frontiers in Immunology, 2022)
Background: Nemolizumab is deemed as a promising drug for atopic dermatitis (AD) patients with pruritus. Objective: To evaluate the efficacy of nemolizumab in treating patients with AD and the association between the dosage or regimen of nemolizumab with the improvement in clinical indices. Methods & Materials: PubMed, Embase, and the Cochrane library were searched for randomized controlled trials (RCTs) published from inception to August 2021. Results: A total of 14 cohorts of participants from six randomized controlled studies were included in the meta-analysis. Nemolizumab significantly reduced the pruritus VAS (WMD=-18.86, 95%CI: -27.57 to -10.15, p<0.001; I2=56.2%, Pheterogeneity=0.005) and EASI (WMD=-11.76, 95%CI: -20.55 to -2.96, p=0.009; I2=0%, Pheterogeneity=0.978) score compared to the placebo. No significant difference was observed in the occurrence of any AEs (RR=1.03, 95%CI: 0.93 to 1.13, p=0.593; I2=0%, Pheterogeneity=0.980) between the two groups. The univariate meta-regression showed that both the dosage and study duration had no association with change of pruritus VAS score. Conclusion: Nemolizumab presented promising effect based on the difference in average change in pruritus VAS and EASI score compared to the placebo. The results indicated its efficacious in relieving pruritus and the severity of AD and improving patients’ quality of life.